การบริหารเชิงกลยุทธกับการปฏิบัติงานวิชาการของโรงเรียนมัธยมศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษา เขต 8 - ทุบจิ๋ว, จิระศักดิ์; เตียเจริญ, สายสุดา (วารสารการบริหารการศึกษา มหาวิทยาลัยศิลปากร, 2017)
การวิจัยนี้มีวัตถุประสงคเพื่อทราบ 1) การบริหารเชิงกลยุทธของรงเรียนมัธยมศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษา เขต 8 2) การปฏิบัติงานวิชาการของโรงเรียนมัธยมศึกษา สังกัดสำนักงานเขตพื้นที่ การศึกษามัธยมศึกษาเขต 8 และ 3) ความสัมพันธระหวางการบริหารเชิงกล ยุทธกับการปฏิบัติงานวิชาการของโรงเรียนมัธยมศึกษา สังกัดสำนักงานเขต พื้นที่การศึกษามัธยมศึกษา เขต 8 กลุมตัวอยางที่ใชในการวิจัย คือ โรงเรียน มัธยมศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษา เขต 8 จำนวน 48 โรงเรียน ผูใหขอมูลโรงเรียนละ 4 คน ประกอบดวย ผูอำนวยการรงเรียน รองผูอำนวยการโรงเรียนฝายบริหารวิชาการ และครูผูสอน 2 คน รวมทั้งสิ้น 192 คน เครื่องมือที่ใชเปนแบบสอบถามเกี่ยวกับการบริหารเชิงกลยุทธของโรงเรียน ตามแนวคิดของพสุ เดชะรินทร และชัยวัฒน หฤทัยพันธและการปฏิบัติงานวิชาการของโรงเรียนมัธยมศึกษา ตามคูมือการบริหารสถานศึกษาขั้นพื้นฐานที่เปนนิติบุคคล ของสำนักงานคณะกรรมการการศึกษาขั้นพื้นฐาน กระทรวงศึกษาธิการสถิติที่ใชในการวิเคราะหขอมูล ไดแก ความถี่ รอยละ คามัชฌิมเลขคณิต สวนเบี่ยงเบนมาตรฐาน และการวิเคราะหคาสัมประสิทธิ์สหสัมพันธของเพียรสัน ผลการวิจัยพบวา : 1) การบริหารเชิงกลยุทธของโรงเรียนมัธยมศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษา เขต 8 โดยภาพรวมและรายดานอยูในระดับมาก เรียงคามัชฌิมเลขคณิตจากมากไปหานอย ดังนี้ การกำหนดทิศทางของ องคการ การนำ กลยุทธไปสูการปฏิบัติ การกำหนดกลยุทธ และการวิเคราะหเชิงกลยุทธ 2) การปฏิบัติงานวิชาการของโรงเรียนมัธยมศึกษา สังกัดสำนักงาน เขตพื้นที่การศึกษามัธยมศึกษา เขต 8 โดยภาพรวมและรายดานอยูในระดับมาก เรียงคามัชฌิมเลขคณิตจากมากไปหานอย ดังนี้ การพัฒนาระบบการประกันคุณภาพภายในสถานศึกษา การแนะแนวการศึกษา การวัดผลประเมินผลและเทียบโอนผลการเรียน การพัฒนาหลักสูตรสถานศึกษาการพัฒนากระบวนการเรียนรู การพัฒนาสื่อนวัตกรรมและเทคโนโลยีเพื่อการศึกษาการพัฒนาแหลงการเรียนรู การนิเทศการศึกษา การสงเสริมความรูดานวิชาการแกชุมชน การสงเสริมและสนับสนุนงานวิชาการแกบุคคล ครอบครัว องคกรหนวยงานและสถาบันอื่นที่จัดการศึกษา การวิจัยเพื่อพัฒนาคุณภาพการศึกษา และการประสานความรวมมือในการพัฒนางานวิชาการกับสถานศึกษาและองคกรอื่น 3) การบริหารเชิงกลยุทธกับการปฏิบัติงานวิชาการของโรงเรียนมัธยมศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษา มัธยมศึกษา เขต 8 มีความสัมพันธกันโดยภาพรวมในระดับสูง อยางมีนัยสำคัญทางสถิติที่ระดับ .01 ซึ่งเปนความสัมพันธแบบคลอยตามกัน THE STRATEGIC ADMINISTRATION AND THE ACADEMIC ADMINISTRATION PERFORMANCE OF SECONDARY SCHOOLS UNDER THE SECONDARY EDUCATIONAL SERVICE AREA OFFICE 8 The purposes of this research were to determine 1) The strategic administration of secondary schools under the Secondary Educational Service Area Office 8, 2) The academic administration performance of secondary schools under the Secondary Educational Service Area Office 8 and 3) The relationship between the strategic administration and the academic administration performance of secondary schools under the Secondary Educational Service Area Office 8. The sample consisted of 48 secondary schools under the Secondary Educational Service Area Office 8. The respondents in each school were an administrator, a vice- administrator of the academic administration performance and 2 teachers totally number of 192 respondents. The instrument was a questionnaire about the strategic administration of secondary schools based on conceptual of Phasu Decharin and Chiyawat Haruethaiphan and the academic administration performance of secondary schools were in the juristic basic educational school administration manual based on the concept of the Office of Basic Education Commission, Ministry of Education. The statistics used in data analysis were frequency, percentage, arithmetic mean, standard deviation and Pearson’s product-moment correlation coefficient analysis. The findings were as follows: 1. The strategic administration of secondary schools under the Secondary Educational Service Area Office 8, as a whole and an individual, were at a high level. In order arithmetic mean from maximum to minimum were as follows; strategic direction setting, strategic implementation, strategic formulation and strategic analysis. 2. The academic administration performance of secondary schools under the Secondary Educational Service Area Office 8, as a whole and an individual, were at a high level. In order arithmetic mean from maximum to minimum were as follows; the development of internal quality assurance performance system of school, the guidance education, the measurement, the evaluation and the credit transfer, the school curriculum, the development of learning process, the development of media innovation and technology for education, the learning resources development, the educational supervision, the promotion of academic knowledge to the community, the promotion of academic and support to individuals, families, organizations, agencies and other schools, the researches to improve the quality of education, and the cooperation in academic development with schools and other organizations. 3. The strategic administration and academic administration performance of secondary schools under the Secondary Educational Service Area Office 8, was found correlated as a whole were at a high level at .01 level of significance which is positive correlated.